IMPLEMENTASI PROGRAM PELESTARIAN SUMBERDAYA KELAUTAN DAN PERIKANAN DI KABUPATEN SITUBONDO - Ismail, M. (Fakultas Ushuluddin dan Filsafat UIN Sunan Ampel Surabaya, 2013)
This study seeks to identify the conservation program of marine resources and fisheries in the Ministry of Marine and Fisheries of Situbondo, how do the effectiveness, and how do the government policies on conservation of marine resources and fisheries in Situbondo. With a descriptive-qualitative approach, the results of this study indicate that the local government through the Ministry of Marine and Fisheries has a major role on preservation of marine resources and fisheries, especially in some big proponent of marine fisheries in Situbondo. The role of government at least can be seen in the form of regulations, policies and implementation of programs were implemented. The role of Government of Situbondo implemented policies Ministry of Marine and Fisheries through programs of conservation of marine and fisheris in Situbondo.